Analysis to ownership innovation modern on patents from the perspective of Positive Law and Fiqh Muamalah - khalid, Afif (Journal of Law Science, 2025)
The rapid advancement of science and technology has given rise to various forms of modern innovations that hold significant economic and strategic value. In this context, patent rights function as a crucial legal instrument to protect intellectual creations. This study aims to analyze the legal construction of ownership over modern innovations within the framework of Indonesian positive law and to compare it with the principles of Islamic jurisprudence (fiqh muamalah). Utilizing a normative juridical method with statutory, conceptual, and comparative approaches, this research reveals that both legal systems recognize intellectual ownership but rest on different epistemological foundations. While Indonesian law emphasizes formal registration and exclusive rights, fiqh muamalah stresses ethical considerations, public benefit (maslahah), and distributive justice. The novelty of this study lies in its proposed integration model that harmonizes national patent law with Islamic legal values. This conceptual synthesis contributes both theoretically and practically by offering a foundation for regulatory reform and the development of a hybrid intellectual property regime that is more just, spiritually grounded, and contextually relevant for Indonesia’s Muslim-majority society.